The degree of the exercise of basic education teachers performing competencies from the point of view of the managers of the schools. "Field Study in the first episode of the schools in the city of Latakia. - Sultan, Manal; Embayed, Muhannad; Ismael, Zeina (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The goal of the current research know the degree of the exercise of basic education teachers performing competencies from the point of view of the managers of the first schools in the city of Latakia. To achieve the goal of the search designed researcher identify composed of (37) distributed on 6 competencies. The researcher used the descriptive approach analytical work, the research sample consisted of (39), teachers of schools in the first episode. The research found the following results: the degree of the exercise of basic education teachers competencies implementation of the lesson, calendar and promote learning, the use of educational materials, the teaching methods and the design of educational activities, were medium. . While the exercise of questions classroom instruction, management were high-grade. In addition, the study indicated that there was no statistically significant difference between the mean scores of the sample due to the gender variable and variable experience The existence of statistically significant differences between the average scores of the sample on the questionnaire of competencies attributed to the variable of the academic qualification (secondary, university, and deepening educational qualification) for the benefit of the managers of the university certificate and deepen the educational qualification.